Latent profile analysis of university students’ self-management and self-monitoring in the links among motivation, engagement, and wellbeing - Zhao, Rui; Ling, Tianye (Frontiers in Psychology, 2022)
This study drew on Garrison’s self-directed learning model for university students in a self-determination theory framework. We adopted a person-centered approach to explore the different combinations of self-management and self-monitoring. Using a sample of Chinese university students (N = 142), we obtained the following data via a self-report survey: autonomous motivation, controlled motivation, self-management, self-monitoring, academic engagement, and wellbeing. Latent profile analysis (LPA) distinguished three self-management and self-monitoring profiles, which are “very low/low,” “high/high,” and “low/very low.” Profiles with a high level of self-management and self-monitoring were positively connected with adaptive outcomes and linked to autonomous motivation. Implications are outlined for theory and practice.